Experimentation: how to test innovative ideas - Chen, Liz (Henry Stewart Talks, 2024)
5-step experimentation process, Framing testable ideas, Defining evidence, Selecting your test, Building the prototype, Executing, analyzing and iterating, Real Talk case study